Factors affecting the competitiveness of livestock products in Ukraine under conditions of russian military aggression - Perehuda, Yuliia (Management and Entrepreneurship: Trends of Development, 2022)
The article is devoted to the formation of new scientific solutions regarding the identification of influencing factors on the competitiveness of Ukrainian livestock products under conditions of Russian military aggression. It has been proven that the livestock industry in Ukraine and its enterprises should increase flexibility and adaptability in terms of ensuring the competitiveness of their products, taking into account changes in the conduct of financial and economic activities under the influence of factors caused by Russian military aggression. The article aims to form a set of factors influencing the competitiveness of livestock products in Ukraine under the conditions of Russian military aggression. Methodology: a complex of general and special methods have been used at the empirical and theoretical levels, such as methods of literary analysis and reverse semantic graphic analysis to determine the essence of the term "competitiveness factor of products of livestock enterprises"; methods of logical generalization and scientific abstraction to determine the classification features of influencing factors on the competitiveness of livestock products in Ukraine under the conditions of Russian military aggression; methods of systematic analysis and synthesis to form a set of factors influencing the competitiveness of livestock products in Ukraine under the conditions of Russian military aggression; methods of systematization, grouping and logical generalization for systematization of information, formation of conclusions and scientific proposals of the article. The article uses systemic, functional, historical, and systemic approaches in revealing and solving the problems of forming a set of influencing factors on the competitiveness of livestock products in Ukraine under the conditions of Russian military aggression. Results: a set of crucial negative and positive factors influencing the competitiveness of livestock products in Ukraine under the conditions of Russian military aggression at the micro, meso, macro, and meta levels has been formed. JEL Classification: О13, Q10.